GREENING OF PRODUCTION: LOGISTICS ASPECTS - Тараєвська, Леся; Галюк, Ірина (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article explores the relevance of greening production and logistics processes in the context of globalization, growing environmental awareness, and the need to ensure sustainable enterprise development. It substantiates that logistics, as a key component of production and distribution chains, significantly impacts the environmental footprint of enterprises through greenhouse gas emissions, excessive resource use, and waste generation. It is determined that the implementation of environmentally friendly practices in logistics activities—such as transportation route optimization, the use of eco-friendly vehicles, the transition to reusable packaging, the development of "green" logistics hubs, and the use of renewable energy sources—is not only an environmental necessity but also a significant competitive advantage. The paper provides a detailed analysis of the role of logistics processes at different stages of the product life cycle, where their share may reach 40–60% of total costs, emphasizing the strategic importance of logistics greening for achieving economic efficiency. The article includes hypothetical calculations of the economic benefits and environmental effects resulting from the implementation of environmental measures in logistics, such as route optimization, the use of reusable packaging, waste sorting and recycling, and the installation of solar energy systems for warehouse operations. The results demonstrate that even basic greening initiatives can lead to significant cost savings, CO₂ emission reductions, and decreased environmental impact. The study concludes that the greening of logistics is an integral part of corporate social responsibility, enhances enterprise competitiveness, fosters a positive brand image, meets the increasing demands of regulatory authorities and environmentally conscious consumers, and contributes to achieving sustainable development goals. Integrating environmental principles into logistics processes is positioned as a strategic direction for modernizing enterprises in response to current economic and environmental challenges.